FAKTOR-FAKTOR MOTIVASI REMAJA BERWIRAUSAHA MELALUI BISNIS ONLINE DI BATUAMPAR PELAIHARI - Akhmad Samhudi; Siti Rizki Pardani (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
The number of conveniences in shopping online and the various types of products and services offered, make the Indonesian people make Online Shops as one of the new